Chinese Opera : The Actor's Craft - Lovrick, Peter, 1953- (Book collections on Project MUSE., 2014)
Chinese opera embraces over 360 different styles of theatre that make one of the richest performance arts in the world. It combines music, speech, poetry, mime, acrobatics, stage fighting, vivid face-painting and exquisite costumes. First experiences of Chinese opera can be baffling because its vocabulary of stagecraft is familiar only to the seasoned aficionado. Chinese Opera: The Actor's Craft makes the experience more accessible for everyone. This book uses breath-taking images of Chinese opera in performance by Hong Kong photographer Siu Wang-Ngai to illustrate and explain Chinese opera stage technique. The book explores costumes, gestures, mime, acrobatics, props and stage techniques. Each explanation is accompanied by an example of its use in an opera and is illustrated by in-performance photographs. Chinese Opera: The Actor's Craft provides the reader with a basic grammar for understanding uniquely Chinese solutions to staging drama.